Gender, violence, and the past in Edda and saga - Clark, David, 1977- (Oxford : Oxford University Press, 2012)
Through thematic concentration on gender/sexuality and violence and generic concentration on Poetic Edda and later texts which rework or allude to it, David Clark provides a diverse but coherent exploration of both key and neglected Norse texts.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Apr. 20, 2012).
Keywords: Old Norse literature -- History and criticism; Gender identity in literature; Violence in literature